Peer-to-peer accommodation in COVID-19 period: A segmentation approach from tourist’s safety perspective - Petruzzi, M. (2022)
This research identifies safety practices to be adopted by organizations of peer-to-peer accommodation for different segments of tourists in a pandemic context. More specifically, it identifies the profiles of tourists based on their opinions on the safety practices they expect to find when booking peer-to-peer accommodation. Results from a Multiple Correspondence Analysis and Cluster Analysis applied to a sample of 864 prospective tourists suggest two prominent dimensions of safety practices: information and hygiene, and protection; and four types of tourist segments: concerned tourists, indifferent tourists, forewarned tourists, and confident tourists. While the concerned tourists value all safety practices most, the indifferent tourists do not require access to information about safety measures, although they do want information on the Covid-19 regulations at their destination. The forewarned tourists attach the least importance to aspects such as information and hygiene, and the greatest to the protection aspect. In contrast, the confident tourists value all information practices and safety measures but do not appreciate the protection aspects. These results will be helpful for peer-to-peer accommodation providers wishing to customize services during and after the Covid-19 period.